EFFECTIVENESS OF FAMILY CAREGIVER-BASED "STROKE CARE" COACHING ON FAMILY READINESS IN CARING FOR FAMILY MEMBERS FAMILY MEMBERS WHO EXPERIENCED A STROKE - Iin Patimah; Andri Nugraha; Tanti Suryawantie (Jurnal Medika Cendikia, 2023)
Introduction: Stroke is one of many non-communicable diseases with a high incidence in Indonesia. So that an intervention is needed that can improve the quality of life of stroke patients to avoid various complications due to stroke. Objectives: This study aims to conduct coaching on stroke care for family members so that the family is better prepared to provide proper care, especially in the rehabilitation phase. Method: the method used in this study was quasi experiment with pretest-posttest with control group design. 26 samples were involved using purposive sampling technique. in the intervention group, coaching was conducted for 4 meetings in 2 weeks, followed by follow-up for 2 weeks, while 13 research samples in the control group received intervention according to program procedures at the hospital. The instruments used were questionnaires and observation sheets. Statistical analysis used Wilcoxon and Mann-Withney tests. Results: for the intervention group there were differences before and after the intervention in terms of knowledge variables (p-value=0.02) and skills (p-value=0.01) while for upper and lower extremity strength there were no differences. Conclusion: Coaching intervention "stroke care" has a significant effect on family readiness for variables of family knowledge and skills in caring for family members who have a stroke in the rehabilitation phase at home.